Effect of Vermicompost and Nitrogen on N, K, Na Uptakes and Growth of Sugarcane in Saline Soil - Djajadi Djajadi; Roni Syaputra; Sulis Nur Hidayati; Yaumil Khairiyah (AGRIVITA, Journal of Agricultural Science, 2020)
Areal cultivation of sugarcane in Indonesia is expanded to soil with high salt content. There is an urgent need to find an appropriate soil amendment fertilizer to minimize negative effect of saline soil on sugarcane growth. The objective of the research was to determine the effect of vermicompost and nitrogen on N, K and Na uptakes and growth of sugarcane grown in saline soil. The treatments consisted of three rates of vermicompost (equivalent to 0, 10, 20 t/ha) and three rates of nitrogen fertilizer (equivalent to 50, 75 and 100 kg N/ha). Nine combinations of treatments were arranged in randomized block design with four replicates. Sugarcane commercial variety of ‘Bululawang (BL)’ was planted for 4 months in soil with Electrical Conductivity (EC) of 4.12 dS/m. Results showed that interaction between vermicompost and nitrogen fertilizer rate increased N, K uptakes and growth of sugarcane in saline soil. Addition amount of vermicompost and nitrogen reduced soil EC and Na/K ratio uptake of sugarcane. In this study, addition of 20 t vermicompost together with 50 kg N/ha induced sugarcane production with the highest biomass during 4 month planted in saline soil.